Co-pyrolysis of plastics and food waste mixture under flue gas condition for bio-oil production - LIm, Huei Yeong; Tang, Shu Hui; Chai, Yee Ho; Suzana, Yusup; Lim, Mook Tzeng (Elsevier Ltd., 2022)
Growing global population increased the energy demand and generation of municipal solid wastes (MSW). MSW can be utilized to produce green renewable fuels via pyrolysis technology. This study investigated the co-pyrolysis of MSW represented by mixtures of food and plastic wastes, in a downdraft pyrolyzer using synthetic flue gas composition. The food wastes in this study included fish and chicken bones, and leftover rice, and plastics included polypropylene and polyethylene (high density and low density) plastics respectively. The effect of pyrolysis temperature and types of feedstocks on the bio-oil yield and quality were determined. Although the highest bio-oil yield was obtained at 400 °C for all feedstocks, GC–MS results indicated major compounds such as fatty acids, esters, amides, nitriles, sugars were more notable at 300 °C. The bio-oil exhibited high water contents due to combustion from the flue gas. Fish bone and plastic mixture has the lowest O/C ratio and the best calorific value of 33.9 MJ/kg compared to the other two feedstocks, however extensive treatments were required to be used as fuel. Overall, bio-oil from this study has the potential to be used as an alternative fuel from co-pyrolysis of food and plastic wastes with further treatments and processing.